Social Media Platforms for Political Mobilization and Citizen Engagement in Democratic Campaigns - Dedy Herianto; Rusydi (Mahogany Journal De Social, 2024)
The present essay is a vehement attempt to explore how effective social media is in regards to political campaigning and participatory campaign movements in democracy. The interviews and focus groups were resorted to, to pursue the information concerning the exposures of the participants of this study to the political contents and their interaction with the created micro-influencers, as well as the implications of the user-generated content (UGC) in general. Logs and diaries were also used. The micro-influencers due to their close interactions with the followers have the most important role of driving political participation as it is stated in the research adopted. Among the examples of social media activism, one may refer to memes, other videos, and realistic campaigns devoted to politics, and it may be concluded as the tool that should never be underestimated to raise the voice of the political force, make people become involved online and offline. To simplify somewhat complicated political issues and engage more viewers, visual effects, in particular emotive photography, and video have been added as the effective means. The cynicism that affects those systems is also reviewed in the paper and the way in which the polarization and fake news interfere with politics and betray the trust in the online media. These give some insights to how social media has affected political activities and participation and social stratification of its citizens and empowered them.